Jump on the cyber bandwagon a 2001 Australian National Training Authority Adult Literacy National Project - final report . - Australia. Department of Education, Training and Youth Affairs; Australian National Training Authority Adult Literacy National Project; West Coast College of TAFE (W.A.) Research and Development Division (Canberra : Dept. of Education, Training, and Youth Affairs, 2002)
This report provides details of the Adult Literacy National Project. Includes information on its background, objectives, achievements, the Program, evaluation and its methodology as well as challenges and solutions.
"Final report for the Department of Education, Training and Youth Affairs from the Research and Development Division West Coast College of TAFE'.
'June 2002'.
Title from title screen (viewed on Jan. 2, 2003).
Text.
Mode of access: Internet via World Wide Web. Available at: http://www.dest.gov.au/ty/litnet/docs/Final%20Rep%20Cyber.pdf
Selected for archiving
Keywords: Adult education -- Australia -- Evaluation; Literacy programs -- Australia -- Evaluation; Literacy -- Australia -- Evaluation